1992
DOI: 10.1021/bi00155a032
|View full text |Cite
|
Sign up to set email alerts
|

Expression of recombinant acetylcholinesterase in a baculovirus system: kinetic properties of glutamate 199 mutants

Abstract: The glycophospholipid-linked, amphiphilic form of acetylcholinesterase (AChE) from Torpedo californica and the hydrophilic form from mouse were overexpressed in Sf9 insect cells using the baculovirus expression system. Recombinant baculovirus, constructed by inserting AChE cDNA's into the genome of Autographa californica nuclear polyhedrosis virus adjacent to the strong polyhedron promoter, yielded recombinant enzyme varying between 0.5 and 3.8 mg/L. The recombinant enzyme was glycosylated although it migrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 35 publications
10
122
1
1
Order By: Relevance
“…On the other hand, replacement of E202 by glutamine resulted in a marked decrease of the phosphylation rates. Radic et al have recently reported similar effects for the reactivity of an analogous mutant of TcAChE (E199Q) with DFP [29]. Again, as for the acylation process, we find that the effect of replacement of E450 on the rates of phosphylation (Table II), parallels that of E202 substitution.…”
Section: Effect Of Mutation On Hydrolysis Of Charged and Uncharged Susupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, replacement of E202 by glutamine resulted in a marked decrease of the phosphylation rates. Radic et al have recently reported similar effects for the reactivity of an analogous mutant of TcAChE (E199Q) with DFP [29]. Again, as for the acylation process, we find that the effect of replacement of E450 on the rates of phosphylation (Table II), parallels that of E202 substitution.…”
Section: Effect Of Mutation On Hydrolysis Of Charged and Uncharged Susupporting
confidence: 82%
“…As shown previously [18], replacement of the aromatic residue Y337 had only a marginal effect on the kinetic parameters (K m and k~at) for the two substrates (Table I) while the corresponding values for hydrolysis of ATC catalyzed by E202Q HuAChE [16], or of the corresponding mutation E199Q in TcAChE [29], differ significantly from those of the wild type enzyme. We now demonstrate that this decrease in catalytic efficiency of E202Q is observed also for the noncharged substrate TB (Table I), This indicates that the effect of replacement of E202 of HuAChE on catalysis is not solely due to electrostatic interactions with the substrate.…”
Section: Effect Of Mutation On Hydrolysis Of Charged and Uncharged Susupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, these results are consistent with the structure and interaction energy calculations, which suggested that Glu202 stabilizes the O-isopropyl moiety of the sarin adduct in a conformation that enables nucleophilic attack on the phosphorus atom by HI-6. Glu202 has previously been reported as a key residue of AChE with an important role in catalysis (21), phosphylation (22), and aging (23). Here, we also observed, in addition to the interaction with the O-isopropyl moiety, an interaction between Glu202 and the methylene of Ser203 with an interaction energy of ∼7 kcal/mol (Table S4).…”
Section: Reactivation Kinetics Measurements Show the Importance Of Glsupporting
confidence: 72%
“…AChEs from Torpedo californica (Radic et al, 1992), Drosophila melanogaster (Chaabihi et al, 1994;Estrada-Mondaca et al, 1998) and rat brain could be actively expressed in satisfactory amounts in a baculovirus-insect cell system ( Table 2). The baculovirus system has severe limitations with respect to the production of larger amounts of protein, but seems to be very suitable for producing mutant recombinant AChEs.…”
Section: Functional Expression Of Recombinant Achesmentioning
confidence: 99%